2011
DOI: 10.1515/cclm.2011.651
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between zinc and insulin-like growth factor 1 (IGF-1), its binding protein (IGFBP-3) and prostate-specific antigen (PSA) in prostate cancer

Abstract: A significantly lowered Zn/tPSA ratio appears to be a sensitive marker of neoplastic lesions, PCa and PIN, regardless of age. In men under 65 years, the Zn/IGF-1 ratio was reduced, depending on the stage of neoplastic lesions (PIN>PCa). These finding can be useful in early diagnosis of prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…Significant decrease was observed (effect size = −1.36; 95% CI, −1.97 to −0.75) using random effects model-meta-analysis of 7 studies [79][85] (2985 cases, 3539 controls, Fig. 4).…”
Section: Resultsmentioning
confidence: 97%
“…Significant decrease was observed (effect size = −1.36; 95% CI, −1.97 to −0.75) using random effects model-meta-analysis of 7 studies [79][85] (2985 cases, 3539 controls, Fig. 4).…”
Section: Resultsmentioning
confidence: 97%
“…However, another recent clinical study has indicated that IGF1 is positively associated and IGFBP3 is inversely associated with allcause mortality in men with advanced prostate cancer (Rowlands et al 2012), indicating that levels of IGF1 and IGFBP3 may have potential as prognostic markers in predicting risk of death in men with advanced prostate cancer. A comparable study has revealed a correlation between zinc, IGF1, and IGFBP3 concentrations, and prostate-specific antigen in prostate cancer, and findings have indicated that zinc, IGF1, and IGFBP3 can be useful in early diagnosis of prostate cancer (Darago et al 2011). In addition, other investigators reported that IGFBP3 gene polymorphism would be associated with the susceptibility to develop prostate cancer (Safarinejad et al 2011a).…”
Section: Ilp Molecules and Cancer Riskmentioning
confidence: 92%
“…IGF2 does not act in isolation during carcinogenesis but is modulated positively and negatively by other components of the system, which may themselves have prognostic value. For example, over-expression of IGF1R is associated with more aggressive tumours (Hakam et al 1999) and IGFBP3 may have a role both in early diagnosis (Darago et al 2011) and prediction of death (Rowlands et al 2012) in prostate cancer and in prediction of risk of colorectal cancer (Wu et al 2011). In view of this, a more accurate assessment of an individual's cancer risk or prognosis may be to combine a panel of measurements as an index.…”
Section: Potential Utilitymentioning
confidence: 99%